Impact of Human-Elephant Conflict: A Case Study from Northern West Bengal, India - Samanta, Dipayan; Sanphui, Priyankar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Human-wildlife conflict (HWC) refers to the conflict between human and wildlife mostly in the edges of protected areas resulting in negative impact on both sides. Elephants are one such animal responsible for HWC in many Asian countries. Northern part of West Bengal encounters large number of instances of Human-elephant conflict (HEC). The present case study was conducted between January 2024 to February 2025, to estimate the impact of HEC on humans in Chauhaddi village of Jalpaiguri District in the Northern West Bengal. Primary data was collected through regular field survey, household questionnaire survey and key informants survey. Results revealed a massive damage of different types of agricultural crops in field during the study period. We also documented instances of house damage and damage of stored food grains by the elephants. Short term measures like use of noise and light or construction of physical barriers and long term managements like maintenance of wildlife corridors, proper restoration of elephant habitat and awareness among locals can help in mitigating HEC in long term. In a nutshell, HEC results in massive loss of crop and property in North Bengal and proper mitigation measures are necessary to address this problem.